PENGEMBANGAN APLIKASI PENGELOMPOKAN ROMBELGAYA BELAJAR SISWA MENGGUNAKANMETODE UX DESIGN THINKING - Aldi Saepurahman, - (2023)
A student's learning style is the most influential internal factor in a student's achievement because it identifies the best way for a student to learn and helps to form academically equitable student groups. However, some counselling teachers in junior high schools explained that they need to spend a lot of time processing learning style test results and inputting all end-of-semester grades to help grouping students for the next school year. Based on this problem, an application for grouping learning style students with average final grades using design thinking was built. The application developed has fulfilled all aspects of user experience from User Experience Questionnaire (UEQ) testing, and obtained a feasibility score through System Usability Scale (SUS) testing of 78.71 when tested on students and teachers in junior high school. The results of testing this application are less than optimal due to the characteristics of students and teachers who lack confidence in using new applications and lack of systematic thinking skills. Researchers suggest that it is necessary to provide more time for users to adapt to the application so that the results of testing this application can be better and increase the feasibility value of SUS testing so that the application is more feasible to use.